Optimization and prediction on mechanical properties of carbon-kenaf reinforced expoy hybrid composites using full experimental and factorial approach - Mohamad Ikhwan Yusuff (Kulliyyah of Engineering, International Islamic University Malaysia, 2020)
The development of hybrid composites from the combination of synthetic and natural fibers have been extensively studied due to their excellent in both mechanical and physical properties. However, the absence of a robust statistical model in predicting and optimizing the optimum mechanical properties based on several parameters, especially fiber content, thickness, and stacking sequences, has caused a problem in designing and producing the hybrid composites. Therefore, the main objective of the current research is to predict and optimize the mechanical properties of fabricated hybrid composites based on these three parameters. Hybrid composite was fabricated by utilizing kenaf fiber (K) and carbon fiber (C) with epoxy matrices. These hybrid composites were fabricated based on three parameters: fiber content (30, 40, and 50 vol.%), thickness (3mm and 5mm), and stacking sequences (CKCKC, CCKCC, CKCK, and KCKCK) using vacuum infusion method in which the ratio of carbon-to-kenaf was fixed to 1:1. The mechanical and physical properties of fabricated carbon-kenaf hybrid composites were investigated. The optimization on mechanical properties of the hybrid composite was then conducted via the multilevel categoric factorial design of experiment (DEO) method. Experimentally, the addition of 30 vol.% to 40 vol.% of fibers has increased the values of tensile, flexural, and impact properties of hybrid composites due to formation of good interaction between fibers and matrix that observed by SEM morphology. Meanwhile, the addition of 50 vol.% fibers has reduced the mechanical properties of carbon-kenaf hybrid composites due to poor interfacial bonding between layers of fibers and epoxy matrix. Besides, the highest tensile and flexural properties were obtained when hybrid composites were fabricated at 3 mm thickness. This is corroborated with the effectiveness of matrix to distribute evenly along the surface of fibers compared to the one with 5 mm thickness of hybrid samples. In terms of stacking sequences, the assignation of carbon fibers as the outer layers exhibit the highest tensile strength, flexural strength, and impact strength with the value of 210.49 MPa, 329.59 MPa, 1143 J/m, respectively as compared to kenaf fiber at 40 vol.% fiber content. Moreover, it can be perceived that the density of carbon-kenaf hybrid composites decreases with an increase in the fiber content and thickness due to the formation of voids and it can be detected by optical microscope (OM) fractography. Additionally, the utilization of kenaf fiber as the outer layer tends to increase the rate of water absorption of hybrid composites in comparison to the carbon fiber as the outer layer due to the hydrophilic nature of kenaf fiber. From the overall findings, ANOVA analysis showed a significant interaction in the developed DOE model in which the result shows that the optimum parameters achieved at 40 vol.% fiber content, 3 mm thickness, and CCKCC stacking sequence. These parameters validated by the fabrication and the obtained values are in the range of predicted values. Therefore, this statistical model offers the great potential of the utilization of carbon-kenaf hybrid composite in structural applications, specifically the automotive industry.